Tracheostomy in Pediatric Intensive Care Unit: Experience from Eastern India - Jain, Mukesh Kumar (Indian J Pediatr, 2020)
OBJECTIVE: Tracheostomy is one of the most commonly used surgical intervention in sick children in the intensive care unit. The literature in the pediatric population is limited, therefore, we conducted this study to evaluate the indications, timing, complications, and outcomes of tracheostomy among the children at our center. METHODS: This retrospective study was conducted from January 2016 through December 2019. Data was collected from the patients’ records and analyzed. RESULTS: During this study period, 283 children were ventilated, of which 26 (9.1%) required tracheostomy. Among this 73% were boys. The median age of the children who underwent tracheostomy was 6.32 y. The most common indication for tracheostomy was prolonged mechanical ventilation [24 cases (92%)] followed by upper airway obstruction [2 cases (8%)]. The average time of tracheostomy was 11.65 d, range (1–21 d). Complications were seen in 14 patients (55%). The most common complications were accidental decannulation, occlusion, pneumothorax, and granulation tissue. Twenty one (80%) patients were successfully discharged, out of which 16 (61%) patients were discharged after decannulation and 5 (21%) were sent home with a tracheostomy tube in situ. Overall mortality in present study was 11.5%; none was directly related to tracheostomy. CONCLUSIONS: The indication for tracheostomy has been changed from emergency to more elective one. Prolonged mechanical ventilation is the most common indication for tracheostomy. Although the timing of tracheostomy is not fixed, two weeks time is reasonable and it can be done safely at the bedside in pediatric intensive care.